Pendekatan fungsional dalam peningkatan mutu berita terjemahan (Jurnal Bahasa, 2004)
This article looks at functional translation as a pragmatic approach in the translation of English news into Malay in the Malay newspapers. Functional translation is one of the most appropriate approaches that can be employed to improve the quality of translated news as the translation is tailored towards the functions and needs of the target audience. According to the functional approach, a news text is translated top-down, i.e., by focussing on the most pragmatic aspects such as the purpose of translation as well as nonns and conventions between the source text and the target text. Once these aspects are satisfied only then will other aspects such as differences between the source language and the target language and the translators intuition are considered. Through such pragmatic approach, the quality and effectiveness of the news is assured as the news if translated appropriately according to the purpose and practical needs of the target audience.